Hubungan Antara Kontrol Diri dan Compulsive Buying pada Remaja Akhir Pengguna Layanan Food Delivery Service di Denpasar - Jonathan, Jonathan (Peneliti.net, 2024)
Late teens, namely in the age range 18 – 23 years, are the age range where teenagers tend to develop shopping habits, one of these shopping habits is compulsive buying (compulsive shopping). There are factors that influence the occurrence of compulsive buying in teenagers, one of which is self-control. This research was conducted to determine whether there is a relationship between self-control and compulsive buying in late adolescents who use food delivery services. The type of research carried out was quantitative research using a one-stage cluster sampling technique involving 147 late adolescents who live in West Denpasar sub-district. Data collection was carried out boldly using a questionnaire consisting of; The Self-Control Scale with a reliability coefficient of 0.896 and the Compulsive Buying Scale with a reliability coefficient of 0.35. Data analysis in this study used a simple linear regression test technique. The results of the simple regression test show a significance value of 0.000 (P<0.05). The results of these values ​​indicate that self-control has a significant influence on compulsive buying of 49.9% (R Square = 0.499; significance value 0.000 < 0.05). Thus, the higher the self-control they have, the lower the level of compulsive buying by young people who use food delivery services in West Denpasar.